2004
DOI: 10.1007/s00125-004-1345-3
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal proliferation within carotid stents is more pronounced in diabetic patients with initial poor glycaemic state

Abstract: Initial hyperglycaemia seems to be a predictor of more pronounced neointimal proliferation after carotid stenting independent of diabetes. As intimal hyperplasia is known to be responsible for stent restenosis, strict optimisation of the hyperglycaemic state should be aimed at before elective carotid artery stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Post-stenting restenoses are typically due to intimal proliferation rather than calcified plaques and caused by exogenic factors (e.g. diabetes mellitus) and inflammatory mediators such as C-reactive protein, platetele derived growth factor among others [14,25] (see Figs. 1 and 2 for typical duplex sonography and DSA finding).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-stenting restenoses are typically due to intimal proliferation rather than calcified plaques and caused by exogenic factors (e.g. diabetes mellitus) and inflammatory mediators such as C-reactive protein, platetele derived growth factor among others [14,25] (see Figs. 1 and 2 for typical duplex sonography and DSA finding).…”
Section: Discussionmentioning
confidence: 99%
“…For stenosis < 50 %, luminal diameter reduction in relation to the distal vessel diameter (NASCET-like criterion) [18] was the main criterion, whereas for stenosis >/= 50 % hemodynamic criteria were used. Intimal hyperplasia was assessed according to Willfort-Ehringer et al [25]. Restenosis was graded comparing results from day one after the procedure with the follow-up results.…”
Section: ■ Doppler and Duplex Sonography Mr And Catheter Angiographymentioning
confidence: 99%
“…52 Finally, there still is the need for identifying specific risk factors for the development of restenosis after CAS. Some studies have identified advanced age, 18 female gender, 18 hyperglycemia, 53 previous treatment with a CEA, 54 and increased serum levels of acute-phase reactants 21 as potential risk factors for the development of a restenosis after CAS; however, the definitive role of these factors remains to be elucidated in larger trials.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller vessel caliber was the principal determinant of in-stent restenosis in the study by West et al (86). Initial hyperglycemia predicted more pronounced neointimal proliferation after carotid stenting in a recent report (88). Advanced glycation end products have been reported to play a role in neointimal formation in animal models of arterial injury, and high serum advanced glycation end product levels may be a risk factor for in-stent stenosis in patients with diabetes (89).…”
Section: Restenosismentioning
confidence: 94%